2015
DOI: 10.1080/15476286.2015.1109768
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 targets Caspase-3 mRNA in activated macrophages

Abstract: To secure the functionality of activated macrophages in the innate immune response, efficient life span control is required. Recognition of bacterial lipopolysaccharides (LPS) by toll-like receptor 4 (TLR4) induces downstream signaling pathways, which merge to induce the expression of cytokine genes and anti-apoptotic genes. MicroRNAs (miRNAs) have emerged as important inflammatory response modulators, but information about their functional impact on apoptosis is scarce. To identify miRNAs differentially expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 63 publications
3
27
0
Order By: Relevance
“…Interestingly, we discovered that LPS-induction of RAW 264.7 macrophages leads to miR-155-mediated CASPASE-3 downregulation and decelerated apoptosis, thereby sustaining macrophage activity (87). This is in agreement with a role of P23 in preventing ER-stress-induced apoptosis (88,89).…”
Section: Novel Rna-binding Proteins In Macrophagessupporting
confidence: 81%
“…Interestingly, we discovered that LPS-induction of RAW 264.7 macrophages leads to miR-155-mediated CASPASE-3 downregulation and decelerated apoptosis, thereby sustaining macrophage activity (87). This is in agreement with a role of P23 in preventing ER-stress-induced apoptosis (88,89).…”
Section: Novel Rna-binding Proteins In Macrophagessupporting
confidence: 81%
“…Several studies showed that miR-155 regulated the production of inflammation mediator via direct target [3638]. In our study, HEK293 cells were cotransfected with the wild-type (WT) or mutated (Mut) SOCS1 luciferase reporter vector, together with miR-155 mimic or miR-NC, for 24 h. Luciferase activity was significantly inhibited in cells transfected with WT SOCS1 and miR-155 mimic, but not in cells transfected with mutation SOCS1 and miR-155 mimic (Figures 5(a) and 5(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it is reported that upregulated miR-155 also exhibits suppressive effects on apoptosis of specific activated inflammatory cells to maintain their critical functions in immune response [27]. MiR-155 also prevents apoptosis in macrophages induced by LPS [28]. Although this phenomenon might be helpful for the host defense against the invasion of pathogens, prolonged life span of inflammatory cells might contribute to excessive inflammatory responses which cause tissue injury.…”
Section: Discussionmentioning
confidence: 99%